Análise de dados sócio-econômicos e sanitários de famílias residentes no distrito-sede de Botucatu (São Paulo, Brasil), em 1969 - Ramos, Maria Iraci Cabianca; Ribeiro, Mário A. Carneiro Leão [UNESP]; Magaldi, Cecília; Iyda, Massako; Almeida, Eurivaldo Sampaio De; Souza, Nelson De (Faculdade de Saúde Pública da Universidade de São Paulo, 1973)
In 1969, a survey was carried out concerning the socio-economical and sanitary aspects of the inhabitants in Botucatu County (S. Paulo, Brazil). Three hundred and five families were interviewed. Data involving the composition of the family, age of the memores, occupation, salary, sanitary conditions of their houses, knowledge about vaccination and their opinions about health services were collected and analysed. Some results were associated with the socioeconomic status of the families. The basic sanitation conditions were adequate and of reasonable standard. Knowledge about the value of vaccination as well as the required doses were vague Resources available for health were fragmented on indication of the lack of coordenation among the health services. Health centers were mainly sought for the care of children, on indication of the population's low degree of knowledge about their purposes. It was concluded that an improvement of the community viewpoints about medical-sanitary aspects is desired and systematic health educaiton programs are necessary and urgent.

Foi realizado, em 1969, um levantamento de dados sócio-econômicos e sanitários da zona urbana de Botucatu. Trezentas e cinco famílias amostradas foram entrevistadas sobre: constituição familiar, idade, ocupação, renda, grau de instrução, condições sanitárias dos domicílios, conhecimento e uso de vacinas, demanda e opiniões relativas aos serviços de saúde. Algumas respostas foram associadas ao status sócio-econômico das famílias. As condições de saneamento básico estavam dentro de padrões quantitativos razoáveis e era alto o desconhecimento sobre o valor e número de doses das vacinas. Constatou-se acentuada dispersão de recursos para saúde, indicando falta de coordenação dos órgãos assistenciais; a demanda ao Centro de Saúde era baixa, quase restrita às crianças, indicando distorsão da percepção da comunidade com relação aos serviços médico-sanitários e necessidade de desenvolvimento adequado desses serviços, além de educação sanitária sistemática.
Socioeconomic and sanitary survey in families living in the Botucatu County (S. Paulo, Brazil) in 1969
Keywords: Socioeconomic survey; Sanitation; Health resortes; Inquérito sócio-econômico; Saneamento do meio; Recurso saúde; Ciências sociais aplicadas